Enhanced microbial respiration due to carbon sequestration in pruning litter incorporated soil reduced the net carbon dioxide flux from atmosphere to tea ecosystem. (15th October 2019) - Pramanik, Prabhat; Phukan, Manabjyoti
Abstract: BACKGROUND: Tea ( Camellia sinensis L.) bushes are periodically (at 3–4 year intervals) pruned (cut from top) to maintain vegetative growth stage and constant height. Plant residues (prunings litter) generated after pruning are generally left in the field as a potential source of organic matter in soil. Organic carbon (C) sequestration due to pruning litter incorporation is expected to increase microbial activity in soil. Being an evergreen plant, tea bushes assimilate atmospheric carbon dioxide (CO2 ) throughout the year; however, the relation between decomposition of pruning litters and net CO2 flux for tea plantation have not been studied before. The objective of this experiment was to evaluate the relation between organic C accumulation and microbial respiration in pruning litters incorporated soil and its subsequent effect on the net CO2 flux from the atmosphere to tea plantation. RESULTS: Tea bushes assimilated 1878.2–2371.2 kg CO2 ha −1 from the atmosphere within December to November; however, pruned bushes assimilated 1451.7–1840.8 kg CO2 ha −1 within the same period. Decomposition of pruning litters added organic matter in soil, which was mostly accumulated in larger soil aggregates having 2.0–0.25 mm size. Such organic matter accumulation significantly increased microbial respiration in those aggregates, which in turn increased the overall rate of CO2 emission from soil to the atmosphere. CONCLUSION: Decomposition of pruning litters leads to emission of 426.5–530.4 kg CO2 ha −1 from soil. Hence, pruned areas recorded relatively lower (16.0–27.4%) net CO2 flux from the atmosphere to tea ecosystem as compared to unpruned tea bushes. © 2019 Society of Chemical Industry